Isolation, Identification and Screening of Antimicrobial Properties of the Marine-Derived Endophytic Fungi from Marine Brown Seaweed - CHANGI WONG; PETER PROKSCH; LEE TUNG TAN; SAMUEL LIHAN; AAZANI MUJAHID; MORITZ MÃœLLER (Indonesian Society for microbiology, 2015)
Marine seaweeds are known to produce valuable medicinal compounds such as antioxidants and anticoagulants, and have been reported to display antimicrobial activity against gram positive and gram negative bacteria. Several studies have identified so-called endophytic fungi living inside their hosts as the source of active compounds. In this study marine brown seaweed, Padina sp., was studied with regards to their endophytic fungi to assess if they are the source of the reported antimicrobial activity. Twenty fungal isolates were isolated from Padina sp. collected off Talang-Talang Island, Sarawak, Malaysia. All isolates were screened for their antimicrobial properties and 11 out of 20 isolates displayed positive results. DNA was successfully extracted for five isolates and sequence analysis grouped all of them with other endophytic fungi. â€œFungus 2â€ seems to be related to a so far uncultured endophytic fungus. â€œFungus 19â€ showed the most promising antimicrobial properties and was chosen for further agar well assay and cytotoxicity testing. Its ethyl-acetate extract showed positive results in the agar well assay and also a cytotoxic effect on Artemia nauplii. The extract was screened using HPLC and showed a compound similar to a known anti-cancer compound, dihydromyricetin, which is also an anti-intoxicant, anti-inflammatory and anti-oxidative agent which may be responsible for the observed antimicrobial activity.